RANCANG BANGUN SKALA KEYAKINAN UNTUK MENYUSUI PADA PEREMPUAN DI BANGKA, INDONESIA - Harsanti, Intaglia; Damayani, Ayi Diah (Poltekkes Kemenkes Bandung, 2023)
Giving breast milk to babies is a choice for a woman. One of the nutritional adequacy rates in infants is obtained from the choice of a woman who decides whether to breastfeed her baby. This study aims to develop a breastfeeding self-efficacy questionnaire for women in Indonesia. The research method used is a mixed method. The research was conducted in Bangka Belitung province in June until December 2021. The initial survey used 115 respondents. Then, proceed with holding FGDs with 8 postpartum mothers. After that, the components of the confidence scale for breastfeeding were obtained and developed into 20 aitems tested on 282 respondents. Based on the results of the confirmatory factor analysis statistical test, it is known that the model complied meets the goodness of fit standard and produces 16 items which are stated to have a loading factor above 0.4. In conclusion, this questionnaire is declared adequate to be used to measure breastfeeding self-efficacy and can be used as initial screening in pregnant or breastfeeding women.